Metastasis of Squamous Cell Carcinoma in the Pelvis of a Dog - Lima, Tiago Barbalho [UNESP]; Leal, Leonardo Martins [UNESP]; Morato, Glaucia Oliveira [UNESP]; Marinho, Paulo Vinicius Tertuliano; Garrido, Eduardo [UNESP]; Moraes, Paola Castro [UNESP]; Nardi, Andrigo Barboza de [UNESP] (Univ Fed Rio Grande Do Sul, 2013)
Background: Squamous cell carcinoma (SCC) is regarded as one of the most common diagnosis in lesions of the digit, should be included in the differential diagnosis of lesions of the digit, and seems to exhibit a distinct behavior. Metastases in bone tissue are rare. Bones such as tibia, ulna and vertebrae have been reported as carcinoma metastasis sites. However, no reports of carcinoma metastasis in pelvic bones of dogs are available. This report aims at describing a case of distant and unusual metastasis of squamous cell carcinoma in the pelvis of a dog after an attempt of surgical resection of the primary lesion in the digit. Case: A six-year-old male Rottweiler dog was referred to the Veterinary Hospital of the Faculdade de Ciencias Agrarias e Veterinarias, Universidade Estadual Paulista, Jaboticabal, Brazil, with a history of a non-healing lesion on the distal medial aspect of the left thoracic limb after amputation of the first digit, which had been performed four months earlier owing to the same problem. Surgical excision of the lesion was performed followed by wound treatment aimed at healing by second intention as an attempt to preserve the limb. Histological analysis revealed a diagnosis of squamous cell carcinoma. There was recurrence of the lesion presented as circular areas with differentiated hemorrhagic tissue amidst the granulation tissue. Another excisional biopsy confirmed squamous cell carcinoma recurrence. After that, the affected limb was amputated with a good recovery. Three months later, the patient was presented with lameness in the left pelvic limb and severe pain in the hip region. Radiographic examination revealed intense periosteal reaction in the body of the left ilium extending to the left sacroiliac joint. Incisional biopsy revealed squamous cell carcinoma metastasis. Due to the clinical presentation, the patient was euthanized and subjected to necropsy. The spleen and lung also exhibited metastatic nodules not detected on previous radiographic examination. Discussion: Squamous cell carcinoma (SCC) is the most common diagnosis in lesions of the digit and this occurrence in Rottweilers is common. Surgical intervention is still the treatment of choice for tumors of the digit. The occurrence of metastases in this patient might be related to the delay in opting for amputation. It has been suggested that the occurrence of metastasis in SCC of the digit is more likely to happen as compared to other parts of the body, but it is not clear why these lesions exhibit a distinct behavior. There are reports of carcinoma metastasis in pelvic bones; however, the primary site was not the digit. The occurrence of this type of bone metastasis is rare and, the few reports found in the literature describe it mostly in the axial skeleton in humans, which is different from what was observed in the case reported here. The most affected sites for metastasis of tumors of epithelial origin are the humerus, femur and spine. SCC should always be considered in the differential diagnosis of lesions of the digit due to its capacity to form metastasis in distant sites. Metastasis can occur in uncommon and less likely sites, such as pelvic bones. After definitive diagnosis, an aggressive treatment is recommended as an attempt to avoid additional complications. Further studies should be conducted with the aim of establishing alternative treatments and management procedures for these patients.
Keywords: squamous cell carcinoma; dog; metastasis; pelvis